2016
DOI: 10.1038/onc.2016.279
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-associated SF3B1 mutants recognize otherwise inaccessible cryptic 3′ splice sites within RNA secondary structures

Abstract: Recurrent mutations in core splicing factors have been reported in several clonal disorders, including cancers. Mutations in SF3B1, a component of the U2 splicing complex, are the most common. SF3B1 mutations are associated with aberrant pre-mRNA splicing using cryptic 3’ splice sites (3’SS) but the mechanism of their selection is not clear. To understand how cryptic 3’SS are selected, we performed comprehensive analysis of transcriptome-wide changes to splicing and gene expression associated with SF3B1 mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 58 publications
4
65
0
Order By: Relevance
“…20 When 23T.G minigene was cotransfected with any of the constructs splicing was observed within exon 10 ( Figure 2C, lanes 8-12). Whereas, when 224C.G minigene was used, only canonical splicing was observed in all cases (lanes [13][14][15][16][17], suggesting that the 23 position relative to cryptic AG is also important for its recognition during the second step of splicing. Further to test branch site utilization, we used ZDHHC16 minigenes with mutated branch sites (WT, 230A.G; mutant, 233 to 235 AAA.GGG).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 When 23T.G minigene was cotransfected with any of the constructs splicing was observed within exon 10 ( Figure 2C, lanes 8-12). Whereas, when 224C.G minigene was used, only canonical splicing was observed in all cases (lanes [13][14][15][16][17], suggesting that the 23 position relative to cryptic AG is also important for its recognition during the second step of splicing. Further to test branch site utilization, we used ZDHHC16 minigenes with mutated branch sites (WT, 230A.G; mutant, 233 to 235 AAA.GGG).…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8] Although the majority of SF3B1 hotspot mutations are located in the Py tract interacting region, the reason for inducing aberrant 39 ss selection through reduced branch site fidelity remains unclear. [9][10][11][12][13] The unique signature of aberrant 39 ss junction usage by SF3B1 mutations suggests that these events can be used as biomarkers to discover additional genomic alterations that lead to similar splicing defects. To this end, we analyzed RNA sequencing (RNA-seq) from 215 CLL patients.…”
Section: Introductionmentioning
confidence: 99%
“…S9D). Similarly, introns with increased retention in the mutant compared to wild-type SF3B1 K562 cell line (Kesarwani et al 2016) or in SF3B1-depleted compared to mock-transfected HeLa cells (Kfir et al 2015) showed higher retention upon IR exposure and DDX54 knockdown (Supplemental Fig. S9E,F).…”
Section: Ddx54 In Genotoxic Stress Responsementioning
confidence: 99%
“…In this study, we made use of nucleolar proteome data sets (Andersen et al 2005;Moore et al 2011), RBP census (Gerstberger et al 2014), DDR genes (Wood et al 2001;Milanowska et al 2011;Mjelle et al 2015), TP53 target genes (Nikulenkov et al 2012;Menendez et al 2013), spliceosomal subcomplexes (Hegele et al 2012), exon-intron-exon regions (Braunschweig et al 2014), and RNA-seq data sets (Kfir et al 2015;Kesarwani et al 2016;Yoshimoto et al 2017). RNA-seq analysis of TCGA data sets (Sebestyén et al 2016) is described in Supplemental Methods.…”
Section: Additional Data Setsmentioning
confidence: 99%
“…Disease-related mutations cluster in proteins involved in spliceosome assembly, particularly ones important for intron recognition, such as SF3B1 (also known as SAP155, SF3b155, and Hsh155p), SRSF1, and U2AF (Yoshida et al 2011;Quesada et al 2012). In disease-related SF3B1 mutants, changes in branch site (BS) usage have been identified (Darman et al 2015;Alsafadi et al 2016;Kesarwani et al 2016); however, the mechanisms by which these mutations affect splicing are largely unknown.…”
mentioning
confidence: 99%